BIOETHICS AND LAW: BEYOND INSTRUMENTAL REASON (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
Many displeasures have been perpetuated throughout the historical process. The perpetuation of hatred and indifference, legitimized by an alleged premise of order and progress, resulted in a series of atrocities. In the name of law and scientific progress, the human person and his relationships were instrumentalized. The other seen not as a subject of law, but as an object of study. Instrumental reason is criticized and the solidification of a new paradigm anchored in citizen premises is proposed. Despite the historical inconveniences, with due study and criticism, it is possible to learn. Deductive method from literature review.